PENGARUH MEDIA AUDIOVISUAL TERHADAP KEMAMPUAN BERARGUMENTASI MAHASISWA PROGRAM STUDI SASTRA CHINA DALAM MATA KULIAH â€œCHINA TODAYâ€ - Yuk Ting Salim (Universitas Warmadewa, 2021)
The achievement of the level of language skills in learning Mandarin at the tertiary level is largely determined by the level of depth of knowledge received by students. The subject